To sleep dreaming medals: Sleep characteristics, napping behavior, and sleep-hygiene strategies in elite track-and-field athletes facing the Olympic Games of Tokyo 2021 - Vitale, J. A.; Borghi, S.; Piacentini, M. F.; Banfi, G.; La Torre, A. (International Journal of Sports Physiology and Performance, 2023)
Purpose: Few data are available on sleep characteristics of elite track-and-field athletes. Our study aimed to assess (1) differences in sleep between sexes and among different track-and-field disciplines, (2) the effect of individualized sleep-hygiene strategies on athletes` sleep parameters, and (3) daytime nap characteristics in track-and-field athletes.